'We Do Not Want Fake Energy': The Social Shaping of a Solar Micro-grid in Rural India. (July 2020) - Sharma, Aviram
During the last two decades, numerous policy actors have advocated multiple models for the diffusion of solar energy-based technologies in India. In recent years, the social development-based energy business model was promoted by some NGOs, civil society groups and academicians for reaching the poor for meeting their energy needs. Using a case study approach, this article explores the social shaping of a solar micro-grid established in rural Bihar through the hybrid model of environmental governance. The article employs the social shaping of technology framework to explain the top-down and bottom-up interpretations of the solar micro-grid in rural India. By focusing on the idea of citizens and consumers, it explains the influence of the wider socio-political context in closing down the debate and stabilising the choices. The article illustrates the implications of the narrow framing of the socio-technical ensemble by the NGO's and civil society groups (top-down perspective) on the diffusion potential of the solar micro-grid. The bottom-up perspective adds more layer to the interpretation of the socio-technical ensemble. An integrated, comprehensive understanding based on both the top-down and bottom-up perspective would help in developing a responsible research and innovation paradigm.